2017
DOI: 10.3389/fnagi.2017.00082
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Difference in Functional Brain Connectivity of Mastication

Abstract: The age-related decline in motor function is associated with changes in intrinsic brain signatures. Here, we investigated the functional connectivity (FC) associated with masticatory performance, a clinical index evaluating general masticatory function. Twenty-six older adults (OA) and 26 younger (YA) healthy adults were recruited and assessed using the masticatory performance index (MPI) and resting-state functional magnetic resonance imaging (rs-fMRI). We analyzed the rs-fMRI FC network related to masticatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 45 publications
(73 reference statements)
2
51
0
Order By: Relevance
“…This has led to the suggestion that any deficit in sensorimotor function in the elderly may be compensated for by the increased involvement of not only sensorimotor cortex but also other CNS regions (eg, prefrontal cortex) involved in cognitive as well as sensorimotor control . This view is consistent with findings that elderly individuals in contrast to young adults have lower masticatory performance scores and less dense connections between mastication‐related cortical sensorimotor areas and cerebellar areas but have denser connections between the sensorimotor cortex and other cortical areas such as the anterior insular and parietal cortex; they manifest more masticatory‐related areas spatially distributed outside the sensorimotor cortex . While these changes may reflect positive adaptive and compensatory neuroplastic changes, it needs to be kept in mind that some of these areas may themselves be subject to detrimental changes with ageing and so their ability to compensate may be compromised.…”
Section: Ageing and Oro‐facial Sensorimotor Functionssupporting
confidence: 61%
See 3 more Smart Citations
“…This has led to the suggestion that any deficit in sensorimotor function in the elderly may be compensated for by the increased involvement of not only sensorimotor cortex but also other CNS regions (eg, prefrontal cortex) involved in cognitive as well as sensorimotor control . This view is consistent with findings that elderly individuals in contrast to young adults have lower masticatory performance scores and less dense connections between mastication‐related cortical sensorimotor areas and cerebellar areas but have denser connections between the sensorimotor cortex and other cortical areas such as the anterior insular and parietal cortex; they manifest more masticatory‐related areas spatially distributed outside the sensorimotor cortex . While these changes may reflect positive adaptive and compensatory neuroplastic changes, it needs to be kept in mind that some of these areas may themselves be subject to detrimental changes with ageing and so their ability to compensate may be compromised.…”
Section: Ageing and Oro‐facial Sensorimotor Functionssupporting
confidence: 61%
“…These various CNS regions have been investigated in laboratory animals, and although there are limited details in humans of the underlying CNS mechanisms that regulate and modulate oro‐facial sensorimotor functions, brain‐imaging investigations using functional magnetic resonance imaging (fMRI) in healthy, dentate young to middle‐aged adult human subjects have resulted in findings generally consistent with findings in laboratory animals. The human studies have shown that chewing and tooth clenching or stimulation of oral implants are associated with increased fMRI‐defined activation of brain regions involved in processing sensorimotor information such as the sensorimotor cortex and cerebellum . It has also been shown that there are dense connections between cortical sensorimotor areas and cerebellar regions that are positively correlated with masticatory performance …”
Section: Regulation Of Oro‐facial Sensorimotor Functionsmentioning
confidence: 99%
See 2 more Smart Citations
“…bilaterally) M1 and S1, and these connections are positively correlated with masticatory efficiency (Fig. ) . However, in edentulous patients (48–72 years old) treated with conventional complete dentures, there is limited activation of these brain regions .…”
Section: Regulation Of Jaw Sensorimotor Functionsmentioning
confidence: 93%